(untitled) (University of Khartoum Journal of Agricultural Sciences, 2025)
A field experiment was conducted for two seasons (1999/2000and 2000/2001), at Shambat Research Station, to investigate the effect ofanthracnose disease incited by Colletotrichum lindemuthianum (Sacc. andMagn.) Bri. and Cavi. in three common bean (Phaseolus vulgaris L.)cultivars. Mean disease incidence of 15.70% was recorded in 1999/2000season and 13.79% in 2000/2001. Mean disease severity of 0.39 and 0.47were recorded in seasons 1999/2000 and 2000/2001, respectively. Meanpod infection in season 1999/2000 was 19.59% and mean seed infectionin the same season was 15.77%. The corresponding results for season2000/2001 were 49.62% and 20.98%, respectively. Mean seed weighreduction was 24.72% in season 1999/2000 and 26.33% in season2000/2001. The introduced cultivar Cranberry out-yielded the two localcultivars in both seasons. The increase in mean yield was 21.13% inseason 1999/2000 and 54.04% in season 2000/2001